Identification and Validation of TEAD Family’s Prognostic Effects and Immune Microenvironment Regulations in Glioma - Zhengyuan Huo; Shaorui Gu; Zheng Bian; Wenli Wang; Zhifeng Jiang (International Journal of Clinical Practice)
Background. Gliomas are primary malignant tumors of the central nervous system. The TEA domain transcription factor (TEAD) family proteins are the ultimate effector molecules of the Hippo pathway. However, their expression and function in gliomas have not been further studied. Methods. This study employed R software as the primary analysis tool. Public databases were used to analyze the expression and prognostic significance of TEADs. Functional enrichment analyses were conducted to determine the functions of the TEADs. We then explored their interaction with tumor-infiltrating immune cells and immune checkpoint proteins (ICPs). A Cox regression model was used to estimate the prognostic value of the TEADs. Finally, we conducted experiments to confirm TEAD3’s function in vitro. Results. TEAD expression was frequently increased in glioma and other malignant tumors. High TEAD expression was found to be substantially linked with isocitrate dehydrogenase (IDH) wild type, noncodeletion of 1p/19q, high WHO grade, and poor prognosis in glioma patients. Functional analyses revealed TEAD involvement in cancer cell transcription. The high expression of TEADs was greatly related to the myeloid-derived suppressor cells (MDSCs) and regulatory T-cells (Tregs) infiltration. TEADs also showed significant correlations with ICP expression in glioma tissues. The Cox regression model demonstrated significant diagnostic and prognostic efficacy in glioma patients. The reduction in TEAD3 affects tumor cell proliferation, migration, invasion, and immune regulation. RNA sequencing disclosed that TEAD3 regulates immune-related pathways, including negative regulation of the CTLA4 inhibitory pathway. Higher TEAD3 expression portended shorter overall survival (OS) and disease-free survival (DFS) in patients with gliomas based on clinical samples. Conclusions. TEADs are overexpressed in gliomas and are associated with a poor prognosis. Importantly, this study discovered that TEADs influence the immunological milieu of glioma by modulating genes associated with immune infiltration.